Body Mass Index as a Prognostic Factor in Resected Lung Cancer: Obesity or Underweight, Which Is the Risk Factor? - Matsunaga, Takeshi; Suzuki, Kenji; Imashimizu, Kota; Banno, Takamitsu; Takamochi, Kazuya; Oh, Shiaki (The Thoracic and Cardiovascular Surgeon, 2015)
Background In general, obesity is thought to be associated with increased surgical mortality and morbidity. On the other hand, low body mass index (BMI) has recently been reported as a poor prognostic factor for surgical candidates. This study investigated the effect of BMI on lung surgery.Methods A retrospective study was conducted on 1,518 consecutive patients who had malignant pulmonary tumors resected between February 2008 and March 2013. BMI was used to classify patients according to the World Health Organization definition: BMI < 18.5: underweight (UW); BMI 18.5 to <25: normal weight (NW); BMI 25 to <30: overweight (OW); and BMI ≥ 30: obese (OB). We defined surgical resection-related mortality as any patient who died within 90 days after resection or while in the hospital. We analyzed morbidity and surgical resection-related mortality, and logistic regression analysis was used to identify predictors for surgical resection-related mortality.Results Among the four groups, the incidence of cerebrovascular complications was 1.5% in UW, 0.4% in NW, 0% in OW, and 0% in OB, and that of pulmonary complications was 13.1% in UW, 8.4% in NW, 7.3% in OW, and 7.6% in OB. Surgical resection-related mortality was 2.9% in UW, 0.6% in NW, 1.7% in OW, and 0% in OB. Multivariate analysis revealed underweight, diffusing capacity of the lung for carbon monoxide, and male sex as the significant predictors.Conclusions In this study, low BMI was an independent risk factor for mortality, and the incidence of cerebrovascular and pulmonary complications tended to be higher in patients with low BMI than in obese patients. Underweight patients should be closely monitored following pulmonary resection.
Keywords: lung cancer treatment (surgery, medical); obesity; surgery; complications